2019
DOI: 10.1186/s13072-018-0252-7
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of DNA hydroxymethylation and DNA methylation in chronic lymphocytic leukemia

Abstract: BackgroundChronic lymphocytic leukemia (CLL) has been a good model system to understand the functional role of 5-methylcytosine (5-mC) in cancer progression. More recently, an oxidized form of 5-mC, 5-hydroxymethylcytosine (5-hmC) has gained lot of attention as a regulatory epigenetic modification with prognostic and diagnostic implications for several cancers. However, there is no global study exploring the role of 5-hydroxymethylcytosine (5-hmC) levels in CLL. Herein, using mass spectrometry and hMeDIP-seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…1 a). Consistent with previous studies, the average gene body profiles revealed a dip around the transcription start site (TSS) and transcription end site (TES) regions [ 30 ].
Fig.
…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…1 a). Consistent with previous studies, the average gene body profiles revealed a dip around the transcription start site (TSS) and transcription end site (TES) regions [ 30 ].
Fig.
…”
Section: Resultssupporting
confidence: 89%
“…5-Hydroxymethylcytosine has been shown to be depleted in various human cancers and is known to be more concentrated in differentiated cells [ 23 , 27 ]. Stem cells, which are closest to the basal epithelial cells in HNSCCs, are known to have lower 5hmC levels, especially in the gene and enhancer regions required for differentiation [ 28 , 30 ]. For our purposes, those differentiation-specific regions would be epithelial and keratinocyte-specific genic and enhancer regions.…”
Section: Discussionmentioning
confidence: 99%
“…2.9 | Methylated DNA immunoprecipitation and hydroxymethylated DNA immunoprecipitation assays MEDIP and hMEDIP assays were performed as previously described. 19,20 The genomic DNA was extracted with a DNA extraction kit (TIANGEN, DP304), and ultrasound was used to break the DNA into DNA fragments about 200 to 600 bp in size. The 5hmC and 5mC DNA fragments were enriched using MEDIP kit (ActiveMotif, 55009) or hMEDIP kit (ActiveMotif, 55010), following the manufacturer's instruments.…”
Section: Reduced Representation Bisulfite Sequencingmentioning
confidence: 99%
“…Interestingly, several studies have associated 5-hmC with transcriptional activation mediated by enhancers, both in embryonic and differentiated cells [28,30]. Like DNA methylation, hydroxymethylation has also been observed to be deregulated in various human pathologies such as degenerative diseases like Parkinson's, Alhzeimer's, and different cancer types [31,36]. In the first thorough study exploring 5 hydroxymethylcytosine…”
Section: Dna Hydroxymethylation In Cllmentioning
confidence: 99%